Fabrication and H2 flux measurement of asymmetric La27W3.5Mo1.5O55.5-δ − La0.87Sr0.13CrO3-δ membranes. Issue 4 (April 2018) - Fontaine, Marie-Laure; Denonville, Christelle; Li, Zuoan; Xing, Wen; Polfus, Jonathan M.; Kvello, Jannicke; Graff, Joachim Seland; Dahl, Paul Inge; Henriksen, Partow P.; Bredesen, Rune
Abstract: Novel asymmetric hydrogen permeable membranes consist of a dense ceramic–ceramic (cercer) composite layer of La0.87 Sr0.13 CrO3-δ and La27 W3.5 Mo1.5 O55.5- δ deposited on a tubular porous support of the latter composition. The membranes were produced by extrusion and dip-coating with various thermal cycles required for adjusting the thermal shrinkage of the different layers and obtaining gas tight membrane layers. The produced asymmetric membranes have a dense cercer layer thicknesses ranging from 25 to 50 μm on supports exhibiting a porosity of up to 40 vol%. The effect of processing parameters, such as volume of pore former, coating steps, sintering temperature and soaking time on the microstructure of the membranes is discussed to highlight critical steps in the manufacturing protocol. Hydrogen fluxes were measured as a function of temperature with both wet and dry Ar sweep gas. Results are discussed with respect to membrane architectures and materials properties.